Joint Land Certification Programmes and Women's Empowerment: Evidence from Ethiopia. Issue 10 (3rd October 2018) - Melesse, Mequanint B.; Dabissa, Adane; Bulte, Erwin
Abstract: This paper connects two important development policy issues: women's empowerment and land certification. We use propensity score matching to study the impact of the Ethiopian joint land registration and certification programme on women's empowerment. Data are collected using surveys and a field experiment, enabling construction of complementary indices for empowerment. Our main result is that joint land certification has significant effects on women's empowerment, particularly on dimensions that indicate female participation and roles outside the home. This result is robust to various sensitivity checks and alternative model specifications.